The Implementation Of The Tilawati Method In Al-Qur'an Learning At Madrasah Diniyah Al-Manshur - Wafa, Ahmad Syariful; Wajdi, Muh Barid Nizarudin; Soedjiwo, Novena Ade Fredyarini; Muzamil, Muzamil; Rosyadi, Moh. Imron (STAI Miftahul Ula Nganjuk, 2024)
This study aims to: explain the implementation of the Tilawati method in Quranic learning at Madrasah Diniyah Al Manshur, identify the supporting and inhibiting factors in Quranic learning at the institution, and evaluate the outcomes of the Tilawati method's application in the learning process. The research employs a qualitative descriptive approach, with the researcher serving as an observer. Data were collected through primary and secondary sources using observation, interviews, and documentation methods. The findings indicate that: 1) The application of the Tilawati method in Quranic learning at Madrasah Diniyah Al Manshur has been effectively conducted, adhering to the guidelines of the Tilawati method. The focus of the learning outcomes is on enhancing students' ability to read the Quran, which involves setting learning targets, conducting learning processes, delivering materials, and performing evaluations. 2) The success of the Tilawati method is supported by adequate facilities and infrastructure, good cooperation among teachers, and students' pre-existing literacy in Quranic reading. However, challenges include varying student abilities and weather conditions. 3) The results of the Quranic learning using the Tilawati method at Madrasah Diniyah Al Manshur show that the method effectively increases students' interest and ability in reading the Quran, as evidenced by assessments conducted during the munaqosyah sessions